Effect of network connectivity on behavior of synthetic Broborg hillfort glasses. Issue 3 (12th November 2022) - Marcial, José; Cicconi, Maria Rita; Pearce, Carolyn I.; Kloužek, Jaroslav; Neeway, James J.; Pokorný, Richard; Vernerová, Miroslava; McCloy, John S.; Nienhuis, Emily T.; Sjöblom, Rolf; Weaver, Jamie L.; Hand, Russell J.; et al.
Abstract: There is wide industrial interest in developing robust models of long‐term (>100 years) glass durability. Archeological glass analogs, glasses of similar composition, and alteration conditions to those being tested for durability can be used to evaluate and inform such models. Two such analog glasses from a 1500‐year‐old vitrified hillfort near Uppsala, Sweden have previously been identified as potential analogs for low concentration Fe‐bearing aluminosilicate nuclear waste glasses. However, open questions remain regarding the melting environment from which these historic glasses were formed and the effect of these conditions on their chemical durability. A key factor to answering the previous melting and durability questions is the redox state of Fe in the starting and final materials. Past work has shown that the melting conditions of a glass‐forming melt may influence the redox ratio value (Fe +3 /∑Fe), a measure of a glass's redox state, and both melting conditions and the redox ratio may influence the glass alteration behavior. Synthetic analogs of the hillfort glasses have been produced using either fully oxidized or reduced Fe precursors to address this question. In this study, the melting behavior, glass transition temperature, oxidation state, network structure, and chemical durability of these synthesized glass analogs is presented. Resulting data suggests that the degree of network connectivity as impacted by the oxidation state of iron impacted the behavior of the glass‐forming melt but in this case does not affect the chemical durability of the final glass. Glasses with a lower degree of melt connectivity were found to have a lower viscosity, resulting in a lower glass transition temperature and softening temperature, as well as in a lower temperature of foam onset and temperature of foam maximum. This lower degree of network connectivity most likely played a more significant role in accelerating the conversion of batch chemicals into glass than the presence of water vapor in the furnace's atmosphere. Future work will focus on using the results from this work with outcomes from other aspects of this project to evaluate long‐term glass alteration models.